The Ages and Metallicities of Early Type Galaxies in the Fornax Cluster - Kuntschner, H; Davies, R (1997)
We have measured central line strengths for a complete sample of early type galaxies in the Fornax cluster, comprising 11 elliptical and 11 lenticular galaxies, more luminous than M_B=-17. In contrast to the elliptical galaxies in the sample studied by Gonzalez (and recently revisited by Trager) we find that the Fornax ellipticals follow the locus of galaxies of fixed age in Worthey's models and have metallicities varying from roughly solar to three times solar. The lenticular galaxies however exhibit a substantial spread to younger luminosity weighted ages indicating a more extended star formation history. We present measurements of the more sensitive indices: C4668 and Hgamma_A; these confirm and re-enforce the conclusions that the elliptical galaxies are coeval and that only the lenticular galaxies show symptoms of late star-formation. The inferred difference in the age distribution between lenticular and elliptical galaxies is a robust conclusion as the models generate consistent relative ages using different age and metallicity indicators even though the absolute ages remain uncertain. The young luminosity weighted ages of the S0s in the Fornax cluster are consistent with the recent discovery that the fraction of S0 galaxies in intermediate redshift clusters is a factor of 2-3 lower than found locally and suggests that a fraction of the cluster spiral galaxy population has evolved to quiescence in the 5 Gyr interval from z=0.5 to the present. Two of the faintest lenticular galaxies in our sample have blue continua and strong Balmer-line absorption suggesting starbursts \la2 Gyrs ago. These may be the low redshift analogues of the starburst or post-starburst galaxies seen in clusters at z=0.3, similar to the Hdelta strong galaxies in the Coma cluster.